Assessment of the feed additive consisting of endo‐1,4‐beta‐xylanase (produced with Trichoderma reesei MUCL 49755), endo‐1,3(4)‐beta‐glucanase (produced with T. reesei MUCL 49754) and polygalacturonase (produced with Aspergillus fijiensis CBS 589.94) (AveMix® 02 CS) for weaned piglets for the renewal of its authorisation and for its extension of use to suckling piglets (AVEVE BV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the feed additive consisting of endo‐1,4‐beta‐xylanase (produced with Trichoderma reesei MUCL 49755), endo‐1,3(4)‐beta‐glucanase (produced with T. reesei MUCL 49754) and polygalacturonase (produced with Aspergillus fijiensis CBS 589.94) (AveMix® 02 CS/ AveMix® 02 CS L) as a zootechnical feed additive for weaned and suckling piglets. The additive is already authorised for use with weaned piglets. This scientific opinion concerns the request for the renewal of the authorisation of the additive for weaned piglets and the extension of use to suckling piglets. The applicant provided evidence that the additive currently in the market complies with the conditions of the authorisation. There was no new evidence that would lead the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) to reconsider its previous conclusions that the additive is safe for weaned piglets, the consumer and the environment under the authorised conditions of use. This conclusion applied also to the new target species (suckling piglets) for which a request for an extension of use was made. The additive in both formulations (powder and liquid) is not irritant to skin or eyes but should be considered a dermal and respiratory sensitiser. There was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation for weaned piglets. The Panel concluded that the additive is efficacious in suckling piglets at 2140 XU, 1230 BGU and 46 PGLU/kg complete feed.